Polarity protein complex Scribble/Lgl/Dlg and epithelial cell barriers. - Su, W.H.; Mruk, D.D.; Wong, E.W.; Lui, W.Y.; Cheng, C.Y. (Advances in Experimental Medicine and Biology, 2012)
The Scribble polarity complex or module is one of the three polarity modules that regulate cell polarity in multiple epithelia including blood-tissue barriers. This protein complex is composed of Scribble, Lethal giant larvae (Lgl) and Discs large (Dlg), which are well conserved across species from fruitflies and worms to mammals. Originally identified in Drosophila and C. elegans where the Scribble complex was found to work with the Par-based and Crumbs-based polarity modules to regulate apicobasal polarity and asymmetry in cells and tissues during embryogenesis, their mammalian homologs have all been identified in recent years. Components of the Scribble complex are known to regulate multiple cellular functions besides cell polarity, which include cell proliferation, assembly and maintenance of adherens junction (AJ) and tight junction (TJ), and they are also tumor suppressors. Herein, we provide an update on the Scribble polarity complex and how this protein complex modulates cell adhesion with some emphasis on its role in Sertoli cell blood-testis barrier (BTB) function. It should be noted that this is a rapidly developing field, in particular the role of this protein module in blood-tissue barriers, and this short chapter attempts to provide the information necessary for investigators studying reproductive biology and blood-tissue barriers to design future studies. We also include results of recent studies from flies and worms since this information will be helpful in planning experiments for future functional studies in the testis to understand how Scribble-based proteins regulate BTB dynamics and spermatogenesis.